2015
DOI: 10.1136/annrheumdis-2015-207483
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of neuropilin-1 as a novel key factor contributing to peripheral microvasculopathy and defective angiogenesis in systemic sclerosis

Abstract: In SSc, NRP1 deficiency may be an additional factor in the perturbed VEGF-A/VEGFR-2 system contributing to peripheral microvasculopathy and defective angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Previous studies have demonstrated that treatment with sera from patients with SSc impairs the angiogenic performance of H-dMVECs in vitro 29 39 40. Nevertheless, whether these antiangiogenic effects may be in part related to the induction of the EndoMT process has never been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that treatment with sera from patients with SSc impairs the angiogenic performance of H-dMVECs in vitro 29 39 40. Nevertheless, whether these antiangiogenic effects may be in part related to the induction of the EndoMT process has never been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Skin biopsies were processed as previously described 28 29. Patient characteristics are summarised in online supplementary table S1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations